An Analysis of Phrasal Verb of Headline News in Online English Newspapers - Fahira, Nadya; Syafrina Prihartini; Linda Astuti Rangkuti (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2023)
The aim of this study were to find out the type of a phrasal verb of headline news in online newspapers and to find out the dominant the findings of thesis research were there every save type of phrasal verb. The study was conducted by using descriptive qualitative method. The data were collected and analyzing by comparing, classifying, categories describing, calculating and displaying by using table. The result of this study found there were five type of a phrasal verb of headline news in online newspapers namely: type of phrasal verb verb transitive ( 69%), separable ( 307,2%) inseparable ( 174,4% ) intransitive ( 207,25 % ) ) inseparable / intransitive (10,2% )The most dominant type of a phrasal verb of headline news in online newspapers used was ta phrasal verb separable